ANALISIS LOCATION QUOTIENT DAN SHIFT-SHARE SUB SEKTOR PERTANIAN DI KABUPATEN PEKALONGAN TAHUN 2013-2017 - Rahayu Mustika Wati; Agus Arifin (Jurnal Ekonomi-Qu, 2019)
This research is secondary data research in the agricultural sub-sectors, those are food crops, horticulture, plantations, animal husbandry, agriculture and hunting services, forestry and logging, and fisheries in Pekalongan Regency in 2013-2017. Pekalongan Regency has arelatively high number of Gross Regional Domestic Product (GRDP) but has the lowest growth rate in the Pekalongan Residency. The purpose of this research is to analyze the basic and nonbasic agricultural sub-sectors, shifts-share in growth agricultural sub-sectors, and analyzingleading agricultural sub-sectors. This research used analysis tools, they were Location Quotient, Shift-Share, and Overlay. The results of this research show that: basic subsectors are plantation and agriculture and hunting services, changes and shifts in the agricultural sub-sector show positive average value and horticulture, forestry and logging, and fisheries sub-sectors have a competitive advantage. Leading agriculture sub-sector in Pekalongan Regency in 2013-2017 was plantation crops.